Pesticide Formulations - Frederick M. Fishel (EDIS)
PI231, a 14-page illustrated fact sheet by Frederick M. Fishel, provides a basic understanding of formulation types and factors a user should consider when selecting a pesticide formulation. Includes a glossary and additional sources of information. Published by the UF Department of Agronomy, June 2010.